Fight Finance

Courses  Tags  Random  All  Recent  Scores

Scores
keithphw$6,001.61
Yuan$1,726.43
Jade$1,665.80
Zin$1,619.43
zy$1,579.70
Carolll$1,522.43
Visitor$1,428.33
Visitor$1,373.33
Visitor$1,323.33
cuiting$1,289.70
Visitor$1,268.61
Visitor$1,251.28
Visitor$1,249.70
Emma Lu$1,100.00
Skywalke...$1,070.00
mm11$1,050.33
Tijo$1,043.33
ninalee$1,039.70
Visitor$1,035.61
Visitor$1,024.70
 

Question 65  annuity with growth, needs refinement

Which of the below formulas gives the present value of an annuity with growth?


Hint: The equation of a perpetuity without growth is: ###V_\text{0, perp without growth} = \frac{C_\text{1}}{r}###

The formula for the present value of an annuity without growth is derived from the formula for a perpetuity without growth.

The idea is than an annuity with T payments from t=1 to T inclusive is equivalent to a perpetuity starting at t=1 with fixed positive cash flows, plus a perpetuity starting T periods later (t=T+1) with fixed negative cash flows. The positive and negative cash flows after time period T cancel each other out, leaving the positive cash flows between t=1 to T, which is the annuity.

###\begin{aligned} V_\text{0, annuity} &= V_\text{0, perp without growth from t=1} - V_\text{0, perp without growth from t=T+1} \\ &= \dfrac{C_\text{1}}{r} - \dfrac{ \left( \dfrac{C_\text{T+1}}{r} \right) }{(1+r)^T} \\ &= \dfrac{C_\text{1}}{r} - \dfrac{ \left( \dfrac{C_\text{1}}{r} \right) }{(1+r)^T} \\ &= \dfrac{C_\text{1}}{r}\left(1 - \dfrac{1}{(1+r)^T}\right) \\ \end{aligned}###

The equation of a perpetuity with growth is:

###V_\text{0, perp with growth} = \dfrac{C_\text{1}}{r-g}###


Copyright © 2014 Keith Woodward